A view at the birdseye nest: African road safety policies at the UNRSC forum - Ramos, M. (5th European Conference of African Studies, 2013)
In May 2011, the UN has innaugurated the Global Decade of Action for Road Safety. This initiative marks a decisive turn in the institutional views on road danger worldwide, strenghning the WHO epidemiologist concept that road accidents causing injuries and deaths are a public health issue to be dealt medically, or rather through the promotion of metaphorical medical discourses and the putting in place of preventing practices. The composition, dynamics and negociative processes of the UNRSC, a mixed UN forum with consultive status for the UN secretary general, directly impact on the national policies connected to the Decade of Action, for it was from such body that this global initiative was funneled, and it is this body that monitors and evaluates it. The present paper proposal offers a sneak view of how the UNRSC was involved in bringing African nation states, African regional organisations and African NGOs to the Decade of Action iniciative, and how difficult it is to gauge the current reality of road risk in Africa from the too abstract and formal world which UNRSC partners inhabit.